Compound-specific carbon and nitrogen isotopic compositions of chlorophyll a and its derivatives reveal the eutrophication history of Lake Zurich (Switzerland) - Naeher, Sebastian; Suga, H.; Ogawa, N.; Schubert, C.; Grice, Kliti; Ohkouchi, N. (Elsevier Science BV, 2016)
© 2016 Elsevier B.V. To reconstruct the impact of eutrophication on phototrophic communities and the biogeochemical cycling of carbon and nitrogen in the surface water, we investigated the distributions and carbon and nitrogen isotopic compositions (d13C and d15N values) of chlorins in the sediments of Lake Zurich. The chlorin distributions were dominated by chlorophyll a (Chl a) and its derivatives, which reflect rapid degradation to the pheopigments in the water column and sediments of the lake. The d13C values of these sedimentary chlorins followed the historical trends of eutrophication and reoligotrophication, except in the surface sediments, which were characterised by higher relative contributions of aged, redeposited organic matter (OM). The d13C values of the sedimentary chlorins together with bulk sediment d13C values and C/N ratios indicate that the phototrophic communities in the lake used a 13C-depleted carbon source, which is mainly of aquatic origin. The d15N values of chlorins reflect the predominance of nitrate assimilating phototrophs, especially the non-N2-fixing cyanobacterium Planktothrix rubescens prevalent during sediment deposition. Shifts in d15N values of Chl a followed mostly the trends in eutrophication and reoligotrophication, but were also affected by community assemblage shifts to diatoms and/or other cyanobacteria at the end of the 19th century and during the eutrophication maximum in the 1970s. The lower d15NChl-a values in the surface sediments coincide with increasing nitrogen to phosphorus ratios and reduced water column mixing that characterise the recent reoligotrophication period and may explain the predominance of P. rubescens in Lake Zurich. In contrast, the higher contributions of laterally transported OM explains the large offset of d15N values of the pheopigments relative to Chl a, which is supported by the high radiocarbon age of the surface sediments.